Peripheral Nerve Stimulation Characteristics of an Asymmetric Head-Only Gradient Coil Compatible with a High-Channel-Count Receiver Array - Lee, Seung-Kyun (Magn Reson Med, 2015)
PURPOSE: To characterize peripheral nerve stimulation (PNS) of an asymmetric head-only gradient coil that is compatible with a commercial high-channel-count receive-only array. METHODS: Two prototypes of an asymmetric head-only gradient coil set, with 42-cm inner diameter, were constructed for brain imaging at 3T with maximum performance specifications of up to 85 mT/m and 708 T/m/s. 24 volunteer tests were performed to measure PNS thresholds with the transverse (X, left/right; Y, anterior/posterior) gradient coils of both prototypes. 14 volunteers were also tested for the Z-gradient PNS in the second prototype, and were additionally scanned with high-slew-rate EPI immediately after the PNS tests. RESULTS: For both prototypes, the Y-gradient PNS threshold was markedly higher than the X-gradient. The Z-gradient threshold was intermediate between those for the X- and Y-coils. Out of the 24 volunteer subjects, only two experienced Y-gradient PNS at 80 mT/m, 500 T/m/s. All volunteers underwent the EPI scan without PNS when the readout direction was set to A/P. CONCLUSION: Measured PNS characteristics of asymmetric head-only gradient coil prototypes indicate that such coils, especially in the A/P direction, can be used for fast EPI readout in high-performance neuroimaging scans with substantially reduced PNS concerns compared to conventional whole-body gradient coils.